Anneal hardening and elevated temperature strain rate sensitivity of nanostructured metals: Their relation to intergranular dislocation accommodation. (15th February 2019) - Renk, O.; Maier-Kiener, V.; Issa, I.; Li, J.H.; Kiener, D.; Pippan, R.
Abstract: Nanocrystalline materials exhibit various properties or phenomena not common in the conventional grain size regime, including enhanced strain rate sensitivity for FCC metals or strength increase during recovery annealing. These peculiarities are associated with the enhanced confinement of plasticity. Accordingly, the interaction of dislocations with the numerous grain boundaries, the boundary state as well as its local chemistry are of importance for a complete understanding. Due to the various influencing factors, determination of the dominant and rate controlling processes remains challenging. Here, we present a study on selected nanostructured FCC materials where dislocation-grain boundary interactions have been studied earlier for their coarse grained counterparts. High temperature nanoindentation revealed for all materials a pronounced increase of strain rate sensitivity when exceeding a certain temperature, peaking prior to the occurrence of significant grain growth. Static annealing of samples close to these peak temperatures leads, for sufficiently small grain sizes, to a maximum hardness increase. Interestingly, despite the nanocrystalline grain size, these temperatures perfectly agree with those obtained earlier for annihilation of lattice dislocations at grain boundaries in coarse-grained samples. This suggests that at elevated temperatures the dominant mechanism controlling the enhanced rate sensitivities in nanocrystalline metals is the thermally activated annihilation of lattice dislocations at grain boundaries. Measurements of activation energies being close to reported values for grain boundary diffusion further support this concept. Graphical abstract: Image 1